Behavior of composite beams with external prestressing in sagging moment regions - Ribeiro, Karla Demoner; Turini, Thiago Tononi; Luchi, Lorenzo Augusto Ruschi e; Calenzani, Adenilcia Fernanda Groberio (Revista IBRACON de estruturas e materiais, 2021)
Abstract Prestressed composite steel-concrete structures are scarcely used due to a lack of clear standardized design guidelines and formulations on the subject. The present research aims to present design methodologies for steel-concrete composite beams with external pretension applied via straight tendons. A computer program to perform structural analysis of such beams was developed based on two different methodologies: the first one is presented in ABNT NBR 8800:2008, in which the guidelines for the design of composite beams with compact webs are adjusted to include the effects of the pretension force. The second methodology is extracted from international literature and presents a structural design process based on stress distribution on the beam. Ninety prestressed and thirty non-prestressed beams were analyzed and designed with the aforementioned computer program to evaluate the influence of beam length, degree of symmetry of the steel profile and eccentricity of the pretension force on the mechanical resistance of the beams. It was observed that, although the prestressing force considerably improved resistance to bending, it introduced high compression stresses on the steel profile; hence, the pre-stressing of composite beams is proved efficient only for steel profiles with symmetrical cross-sections. Resumo A protensão em estruturas mistas de aço e concreto é pouco utilizada pela falta de normas e formulações claras sobre o assunto. Esse trabalho visa apresentar metodologias de análise e dimensionamento de vigas biapoiadas mistas de aço e concreto com protensão externa e cabo de traçado reto (pré-tração). Um programa computacional que efetua a análise e o dimensionamento dessas vigas foi elaborado com base em duas metodologias distintas: a da ABNT NBR 8800:2008, de vigas mistas compactas, ajustada para incluir os efeitos da força de protensão e uma segunda, extraída da literatura internacional, em que o dimensionamento é feito por meio da verificação das tensões atuantes. Noventa vigas mistas protendidas e trinta sem protensão foram calculadas por meio do programa computacional desenvolvido para avaliar a influência do comprimento do vão, do grau de monossimetria da seção transversal do perfil de aço e da excentricidade da força de protensão na capacidade resistente das vigas. Observou-se que embora a protensão gere uma melhora considerável no comportamento à flexão, a força de protensão introduz altas tensões de compressão no perfil de aço, por isso a eficiência da protensão foi comprovada apenas nos casos de vigas mistas com perfil de aço duplamente simétrico.